APPROPRIATE DOSE ROUNDING OF CYTOKINE MODULATORS FOR PAEDIATRIC RHEUMATOLOGY INPATIENTS. Issue 9 (17th August 2016) - Paget, Chris
Abstract : Background: Cytokine modulators (adalimumab, infliximab, etanercept, anakinra, canakinumab, rituximab, tocilizumab and abatacept) are high-cost biologics used primarily in paediatrics to treat patients with juvenile idiopathic arthritis.1 Funding mechanisms are unreliable and inconsistent hence appropriate dose rounding is a key cost-saving measure.2 However, there is a lack of evidence-based guidance for dose rounding in paediatrics.3 Aims and objectives: Determine if 100% of inpatient cytokine modulator prescriptions in rheumatology are dose rounded up or down to the nearest whole vial, pen or syringe if within 5 or 10% of the dose for patients less or more than 10 kg respectively. Establish financial impact of drug wastage due to failures in dose rounding. Method: Retrospective data collection of electronic prescriptions for all cytokine modulators prescribed for rheumatology inpatients from January 2011 to December 2014. Prescriptions analysed using a five step process to determine if doses could have been rounded to nearest whole dose unit. Cost of waste resulting from failure to dose round also calculated. Results: Only 35% (380/1100) of prescriptions rounded to the nearest whole dose unit therefore audit standard not met. 97% (698/720) of all prescriptions not dose rounded were for tocilizumab and infliximab with approximate annual wastage of £11, 000. Unexpected and significant unavoidable wastage identified due to lack of paediatric-friendly dose unit sizes, particularly for canakinumab (approximately £740, 000/year). Discussion: Appropriate dose rounding does not appear to be common practice. Raising awareness and educating rheumatology and pharmacy teams as well as establishing local dose banding or rounding guidelines may improve future results. Tocilizumab is available in 80 mg, 200 mg and 400 mg vials therefore there is scope for flexibility in dose rounding if combinations are used appropriately. Unavoidable waste may be reduced through use of pharmacy central intravenous additive service (CIVAS) for preparation or use of biosimilars.